Predictive value of scoring systems for the diagnosis of acute appendicitis in emergency department patients: Is there an accurate one? - AKOĞLU, HALDUN; ONUR, ÖZGE ECMEL (SAGE PUBLICATIONS LTD, 2020)
Background: Acute appendicitis is one of the challenging surgical conditions presented in the emergency departments. Clinical scoring systems were developed to reduce the negative appendectomy rate and also to avoid unnecessary diagnostic evaluation. Objectives: The primary aim was to compare the clinical adequacy of the Alvarado, Acute Inflammatory Response, and the Raja Isteri Pengiran Anak Saleha Appendicitis scores in patients with right lower quadrant pain for the diagnosis of acute appendicitis. Methods: This was a prospective and observational study. All patients over the age of 18 years who presented with a complaint of right lower quadrant pain were enrolled. The Alvarado, Acute Inflammatory Response, and Raja Isteri Pengiran Anak Saleha Appendicitis scoring systems were compared. The patients were either admitted or followed-up as out-patient. Face-to-face or telephone follow-up visits were arranged for the patients who did not have surgery and who were not admitted. Results: 232 patients were included and 14 patients were excluded from the study. Of the 218 patients, 114 patients underwent surgery. Of the 114 patients, 107 patients were pathologically diagnosed with acute appendicitis. It was determined that Raja Isteri Pengiran Anak Saleha Appendicitis score was the most valuable score with 0.88 accuracy, followed by Acute Inflammatory Response (area under the curve = 0.79) and Alvarado (area under the curve = 0.71) scores. Conclusion: The accuracy of Raja Isteri Pengiran Anak Saleha Appendicitis scoring system was higher for the diagnosis of acute appendicitis than the other scores. The cut-off of the Raja Isteri Pengiran Anak Saleha Appendicitis score from a 7.5-point threshold provides a practical, non-invasive, rapid diagnostic method that increases acute appendicitis discriminative power in patients presenting with right lower quadrant pain.
Keywords: Appendicitis; Alvarado; Acute Inflammatory Response; Raja Isteri Pengiran Anak Saleha Appendicitis; abdominal pain; INFLAMMATORY RESPONSE SCORE; ANAK SALEHA APPENDICITIS; RIPASA SCORE; ALVARADO SCORE